(Un)conditional consumer protections in high‐cost lending regulation: Impacts on local lending geographies. Issue 4 (3rd September 2022) - Bea, Megan Doherty; Bley, K.
Abstract: Regulation of small‐dollar lending in the United States is heterogeneous, leaving open the question about what policy designs work best for protecting consumers. We compare the effectiveness of regulations that include a consumer eligibility component and regulations that apply to all consumers, centering our analyses on communities with disproportionate exposure to high‐interest lending storefronts. Specifically, we compare how the Military Lending Act (MLA), which provided military‐specific protections, and statewide policies affected high‐cost lender activity in military communities in three states. We find that statewide regulations were effective in reducing the number of high‐cost lenders within local communities across states, including military communities, while the MLA had no impact on the number of lenders around military bases. Our findings have implications for how to regulate small‐dollar lending and protect consumers at increased risk of exposure to high‐cost lending, with specific attention to product alternatives and access to low‐cost financial services.